PENERAPAN PEMBELAJARAN INKUIRI TEKA–TEKI BERGAMBAR UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI SMA HANDAYANI PEKANBARU - Fitriani, Nabsiah; Miharty, Miharty; Anwar, Lenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve student’s achievement on the subject of  koloid  class XI in SMA Handayani Pekanbaru by applying Inquiry Pictorial Riddle. The research conducted is a research experiment cuasi with pretest-posttest design. Sample consists of two classes, XI IPA 2 as control class and XI IPA 1 as experiment class randomly selected after testing the homogeneity. Experiment class is a class that is treated by applying Inquiry Pictorial Riddle. Data analysis technique used is test-t. Based on research results obtained by the end of the data processing tcount > ttable is  2,46 > 1,67, that means application of Inquiry Pictorial Riddle  can improve student achievement on the subject of koloid class XI in SMA Handayani Pekanbaru. The improvement of learning achievement in the experiment class was supported by the influence coefficient value of 6,3%. Key Words: Inquiry Pictorial Riddle, learning achievement, koloid